PI3Kδ Inhibition Enhances the Antitumor Fitness of Adoptively Transferred CD8+ T Cells - Bowers, Jacob S.; Majchrzak, Kinga; Nelson, Michelle H.; Aksoy, Bulent Arman; Wyatt, Megan M.; Smith, Aubrey S.; Bailey, Stefanie R.; Neal, Lillian R.; Hammerbacher, Jeffrey E.; Paulos, Chrystal M. (Frontiers in Immunology, 2017)
Phosphatidylinositol-3-kinase p110δ (PI3Kδ) inhibition by Idelalisib (CAL-101) in hematological malignancies directly induces apoptosis in cancer cells and disrupts immunological tolerance by depleting regulatory T cells (Tregs). Yet, little is known about the direct impact of PI3Kδ blockade on effector T cells from CAL-101 therapy. Herein, we demonstrate a direct effect of p110δ inactivation via CAL-101 on murine and human CD8+ T cells that promotes a strong undifferentiated phenotype (elevated CD62L/CCR7, CD127 and Tcf7). These CAL-101 T cells also persisted longer after transfer into tumor bearing mice in both the murine syngeneic and human xenograft mouse models. The less differentiated phenotype and improved engraftment of CAL-101 T cells resulted in stronger antitumor immunity compared to traditionally expanded CD8+ T cells in both tumor models. Thus, this report describes a novel direct enhancement of CD8+ T cells by a p110δ inhibitor that leads to markedly improved tumor regression. This finding has significant implications to improve outcomes from next generation cancer immunotherapies.